2021
DOI: 10.1186/s12935-021-02313-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of busulfan plus melphalan-based versus melphalan 200 mg/m2 conditioning regimens for autologous hematopoietic stem cell transplantation in patients with multiple myeloma: a systematic review and meta-analysis

Abstract: Background High-dose melphalan (HDMEL, 200 mg/m2) is considered as the standard conditioning regimen for autologous hematopoietic stem cell transplantation (auto-HSCT) in multiple myeloma (MM). However, whether the combination of melphalan with busulfan (BUMEL) conditioning outperforms HDMEL remains controversy. Accordingly, a systematic review and meta-analysis was carried out to compare the outcomes of HDMEL and BUMEL-based conditioning regimens in newly diagnosed MM patients having undergone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The international standard for high‐dose chemotherapy before AHSCT remains melphalan at 200 mg/m 2 (Mel200) in both the up‐front and salvage second AHSCT settings. Yet intensified regimens containing busulfan, thiotepa or bendamustine with melphalan have recently challenged the Mel200 standard 3–6 …”
Section: Introductionmentioning
confidence: 99%
“…The international standard for high‐dose chemotherapy before AHSCT remains melphalan at 200 mg/m 2 (Mel200) in both the up‐front and salvage second AHSCT settings. Yet intensified regimens containing busulfan, thiotepa or bendamustine with melphalan have recently challenged the Mel200 standard 3–6 …”
Section: Introductionmentioning
confidence: 99%
“…Busulfan is the most commonly used drug for hematopoietic stem cell transplantation [8]. Several studies have confirmed that the conditioning regimen containing busulfan is equivalent to HDMEL in patients with MM in ASCT [9][10][11][12]. A number of investigations have explored the role of busulfan and the cyclophosphamide (BU/CY) regimen in MM allogeneic hematopoietic stem cell transplantation (allo-HSCT) and proved to be safe and reliable [13].…”
Section: Introductionmentioning
confidence: 99%